STUDY OF THE MAIN DIFFERENCES BETWEEN UZBEKISTAN’S ACCOUNTING STANDARD NO. 4 “INVENTORIES” AND IAS 2 (INVENTORIES), AND WAYS TO HARMONIZE THEM - Pashaxodjayeva Dildora Djabborxonovna; Toshnazarov Bobur Shuhratilloyevich (JOURNAL OF NEW CENTURY INNOVATIONS, 2026)
Annotation: This study examines the main differences between Uzbekistan’s Accounting Standard No. 4 “Inventories” and IAS 2 (Inventories). The research focuses on key aspects such as recognition, measurement, cost determination, valuation methods, impairment, and disclosure requirements. By conducting a comparative analysis, the paper identifies methodological and practical gaps between national accounting regulations and International Financial Reporting Standards (IFRS). The study also explores the challenges faced by Uzbek entities in the process of transitioning to international standards. Based on the findings, practical recommendations are proposed to harmonize national accounting practices with IAS 2, enhance transparency, improve financial reporting quality, and support the integration of Uzbekistan’s accounting system into the global financial environment.